A wavelet analysis for crack location detection on cantilever beam - Muhammad 'Afif, Mohamed Azmi (2013)
Over the last few decades, the damage identification methods of civil and mechanical structures have been drawing much interest from various fields. Wavelet analysis, a relatively new mathematical and signal processing tool, is one of such methods that have been studied recently. It is a time–frequency analysis that provides more detailed information about non-stationary signals which traditional Fourier analysis miss. This rather new method has been applied to various fields including civil, mechanical and aerospace engineering, especially for damage detection. The purpose of this paper is to provide the review of the research that has been conducted on damage detection by wavelet analysis. First, the theory of wavelet analysis is presented including continuous wavelet transform followed by its application. This paper proposes damage detection in beam-like structures with small cracks, whose crack ratio [r = Hc/H] in between 10% to 20%, without baseline modal parameters. The approach is based on the difference of the continuous wavelet transforms (CWTs) of two sets of mode shape data which correspond to the uncrack cantilever beam with the crack cantilever beam. The mode shape data of a cracked beam are apparently smooth curves, but actually exhibit local peaks or discontinuities in the region of damage because they include additional response due to the cracks. The modal responses of the crack cantilever beams used are computed using the modal testing method. The results demonstrate whether the crack can be detect on the cantilever beam using the CWT, and they provide a better crack indicator than the result of the CWT of the original mode shape data. The effects of crack location and sampling interval are examined. The experimental and the analysis results show that the proposed method has great potential in crack detection of beam-like structures as it does not require the modal parameter of an uncrack beam as a baseline for crack detection. It can be recommended for real applications